Progesterone receptors in the thymus are required for thymic involution during pregnancy and for normal fertility - Tibbetts, Todd A. (The National Academy of Sciences, 1999)
Thymocyte development is reported to be inhibited by pregnancy, although the impact of this effect on fertility is unknown. We demonstrate, using progesterone receptor null mutant mice, that the inhibitory effects of pregnancy hormones on T cell development require the presence of functional progesterone receptor (PR). A combination of hysterectomy, thymic immunohistochemistry, and transplant studies reveals that local expression of PR in thymic stromal cells is specifically required for thymic involution to occur. These cells, under the influence of progesterone, block T cell development at the early pre-T cell (CD3(−)CD44(+) CD25(+)) stage of development via a paracrine mechanism. In addition, age-related thymic involution is shown to occur by a separate PR-independent mechanism. Finally, pregnancy studies with thymic transplants from progesterone receptor null mutant mice to wild-type female recipients demonstrate that thymic stromal PR is required for normal fertility. Together, these observations provide evidence for a PR-dependent paracrine mechanism that blocks very early T cell lymphopoiesis during pregnancy and is essential for normal fertility.